Utilization of Toxic Plant by the Community in Bulu Sub-district, Rembang Regency, Central Java - Prabawati, Tyas; Siswoyo; Haneda, Noor Farikhah (Journal of Tropical Silviculture, 2025)
Until this day there are few number of people who take advantage of toxic plants and a lot of potentioal of toxic plants are unknown. The aims of this study were to assess the toxic plant species and examine the utilization of poisonous plants in  District of Bulu, Rembang, Central Java. The method employed were FGD (Focus Group Discussion), interview, exploration and literature study. This study obtained 28 species of toxic plants from 19 families. The species that are widely used are Apocynaceae, Euphorbiaceae and Fabaceae. Habitus and parts of toxic plants that are used the most are the herbs and all parts. Utilization of toxic plants are for pesticides, medicines, food, ornamental plants, pest barriers, animal feed, economy, trust, craft and furniture. Treatments of toxic plants according to the utilization are utilizing the toxic, eliminating the toxic, or utilizing the untoxic part or part of which the toxic is not obtained.